Հայ֊սպանական մշակութային կապերու դրուագներ (ԺԹ. դար-1930ականներ) - Բախչինեան, Արծուի (տպ. Atlas)
The article explores significant episodes of Armenian-Spanish cultural relations from the 19th century to the 1930s, divided into three main sections. The first section, “Literary Connections,” highlights Spanish themes in the works of Armenian authors and the initial translations of Spanish literature into Armenian. The section “Armenian Intellectuals and Artists in Spain” focuses on notable Armenian figures, including Vardges Surenyants, Vahram Papazyan, Kostan Zaryan, and Armen Ohanian, who traveled to Spain, drawing inspiration from its culture and integrating it into their work. The final section, “Cultural Relations in Soviet Armenia,” discusses particularly the period during the Spanish Civil War (1936-1939), when Soviet-Armenian publications featured extensive writings on Spain and its art. Armenian writers began to compose works about the Spanish people’s struggle, and Spanish cultural events were organized in Yerevan. These accounts of Armenian-Spanish cultural connections demonstrate the mutual appreciation between two geographically distant nations with limited historical interaction, showcasing several notable episodes of cross-cultural recognition.
Keywords: Արուեստ; Մշակութային կապեր